Pengaruh Kepercayaan Diri dan Gaya Belajar terhadap Hasil Belajar Matematika - Gossani Puja Lestari; laila hayati; eka kurniawan; Amrullah (Griya Journal of Mathematics Education and Application, 2022)
This research aims to find out the influence of self-confidence on students mathematics learning outcomes, to find out the influence of learning style on students mathematics learning outcomes, and to find out the influence of self-confidence and learning style on students mathematics learning outcomes of 8th grade SMP Negeri 2 Kediri academic year 2021/202. This type of research was ex post facto. The population of this research were all students of 8th grade as many as 55 students consisting of 2 classes, namely class VIII A and class VIII B. The sample used was a sample of saturation or total sampling where the entire population was sampled in this research. Data collection techniques in this research using questionnaire and test questions. The instrument of this research was in the form of a self-confidence questionnaire, learning style questionnaire, and a test questions of students mathematics learning outcomes of 8th grade SMP Negeri 2 Kediri. From the data analysis obtained, there was found an inflence of self-confidence on students mathematics learning effect of 8th grade SMP Negeri 2 Kediri with the coefficient of determination of 7,4%. Then for learning style there was not found an influence on students mathematics learning effect of 8th grade SMP Negeri 2 Kediri with the coefficient of determination of 0,2%. The results of data analysis also showed that there was not a significant effect between students self-confidence and learning style on students mathematics learning effect of 8th grade SMP Negeri 2 Kediri with the coefficient of determination of 7,6%.